2012
DOI: 10.2527/jas.2011-4657
|View full text |Cite
|
Sign up to set email alerts
|

Associations between weather conditions during the first 45 days after feedlot arrival and daily respiratory disease risks in autumn-placed feeder cattle in the United States1

Abstract: Data on associations between weather conditions and bovine respiratory disease (BRD) morbidity in autumn-placed feedlot cattle are sparse. The goal of our study was to quantify how different weather variables during corresponding lag periods (considering up to 7 d before the day of disease measure) were associated with daily BRD incidence during the first 45 d of the feeding period based on a post hoc analysis of existing feedlot operational data. Our study population included 1,904 cohorts of feeder cattle (r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 56 publications
(52 citation statements)
references
References 10 publications
(11 reference statements)
1
42
0
5
Order By: Relevance
“…Nonetheless, the fitted models indicated that induction weight was important after controlling for breed, sex, source region and other covariates. Although previous studies have reported increased risk with reduced mean cohort weight (Cernicchiaro et al, 2012a;Cernicchiaro et al, 2012b, c), these studies used group-or cohort-level analyses and did not adjust for animal-level weight. By fitting both animal level and mean cohort-level induction weight in the same model, we have assessed the contextual effect of induction weight.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Nonetheless, the fitted models indicated that induction weight was important after controlling for breed, sex, source region and other covariates. Although previous studies have reported increased risk with reduced mean cohort weight (Cernicchiaro et al, 2012a;Cernicchiaro et al, 2012b, c), these studies used group-or cohort-level analyses and did not adjust for animal-level weight. By fitting both animal level and mean cohort-level induction weight in the same model, we have assessed the contextual effect of induction weight.…”
Section: Discussionmentioning
confidence: 99%
“…Because peak BRD incidence typically occurs between 2 and 4 weeks after induction and weather variables are thought to have a lagged effect (Cernicchiaro et al, 2012a), the weather variables analysed in the current study were estimated for the first week from day 0 (i.e. including day 0 to day 6).…”
Section: Exposure Variablesmentioning
confidence: 99%
See 3 more Smart Citations